Preserving Cultural Heritage Through Sasando Performance Art Management - Natonis, Rolfi Junyanto; Hartono, Hartono; Saearani, Muhammad Fazli Taib Bin (Gorga : Jurnal Seni Rupa, 2024)
Sasando is a traditional musical instrument typical of Rote Island, Indonesia which is currently threatened with extinction. One effort to preserve this cultural heritage is through Sasando Performing Art Management. This study aims to analyze Sasando Performing Art Management strategies in efforts to preserve cultural heritage. The research method used is a qualitative case study by collecting data through interviews, observations, and documentation studies. The results showed that there were four main components in Sasando performance art management, namely planning, organizing, implementing, and supervising. At the planning stage, the identification of potential, SWOT analysis, and determining conservation goals.